2010
DOI: 10.1136/hrt.2009.185025
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous closure of hypertensive ductus arteriosus

Abstract: Percutaneous treatment of hypertensive PDA is safe and effective. ADO works well for most cases, but sometimes other devices (MVSDO or ASO) have to be used. When cases are selected adequately, pulmonary pressures decrease immediately and continue to fall with time.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
26
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(29 citation statements)
references
References 21 publications
2
26
0
1
Order By: Relevance
“…The results of the present study are comparable with available studies (Table ) and showed that the closure of the PDA with PAH is feasible, safe, and efficacious at all age groups with marginally increased risk of device embolization . The most important dilemma in these patients is whether to close or not to close the PDA, because of the risk of progressive pulmonary vascular disease .…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…The results of the present study are comparable with available studies (Table ) and showed that the closure of the PDA with PAH is feasible, safe, and efficacious at all age groups with marginally increased risk of device embolization . The most important dilemma in these patients is whether to close or not to close the PDA, because of the risk of progressive pulmonary vascular disease .…”
Section: Discussionsupporting
confidence: 86%
“…May be in such cases before using large muscular septal occluder, which are difficult to retrieve, it is better to do the balloon sizing to measure the distended size of the duct. In older age group, MVSDO closure is reasonably good option and has been found to be safe . The problem arises in small infants with large PDA because over sizing is not feasible in this subset.…”
Section: Discussionmentioning
confidence: 99%
“…[17][18][19][20][21] In patients with a large PDA and severe PAH, percutaneous closure of the PDA has some advantages over conventional surgery: for example, this procedure avoids the deleterious consequences of thoracotomy and general anesthesia in teenage and adult patients. Most importantly, real-time hemodynamic changes can be monitored during the procedure.…”
mentioning
confidence: 99%
“…Late presentation in developing countries means that many patients have a level of pulmonary hypertension that could make intervention dangerous. The results from a study in Mexico 84 are important and encouraging. They reported 168 patients with isolated patent ductus arteriosus (PDA) and pulmonary artery systolic pressure ≥50 mm Hg.…”
Section: Global Burden Of Cardiovascular Diseasementioning
confidence: 95%